Neuroimaging of the Philadelphia Neurodevelopmental Cohort - Satterthwaite, Theodore D.; Elliott, Mark A.; Ruparel, Kosha; Loughead, James; Prabhakaran, Karthik; Calkins, Monica E.; Hopson, Ryan; Jackson, Chad; Keefe, Jack; Riley, Marisa; Mentch, Frank D.; Sleiman, Patrick; et al. (NeuroImage (Orlando, Fla.), 2014)
The Philadelphia Neurodevelopmental Cohort (PNC) is a large-scale, NIMH funded initiative to understand how brain maturation mediates cognitive development and vulnerability to psychiatric illness, and understand how genetics impacts this process. As part of this study, 1445 adolescents ages 8–21 at enrollment underwent multimodal neuroimaging. Here, we highlight the conceptual basis for the effort, the study design, and the measures available in the dataset. We focus on neuroimaging measures obtained, including T1-weighted structural neuroimaging, diffusion tensor imaging, perfusion neuroimaging using arterial spin labeling, functional imaging tasks of working memory and emotion identification, and resting state imaging of functional connectivity. Furthermore, we provide characteristics regarding the final sample acquired. Finally, we describe mechanisms in place for data sharing that will allow the PNC to become a freely available public resource to advance our understanding of normal and pathological brain development. •The PNC is a large-scale study of neurodevelopment, with 1445 subjects imaged.•Measures span multi-modal MRI, genomics, and testing of cognition and psychopathology.•The PNC will be a public resource to study normal and pathological brain development.